CULTURAL CODES IN POLITICAL DISCOURSE: LINGUISTIC SIGNIFICANCE AND INTERPRETATIVE DIMENSIONS - Sultonov Temurbek Uyg’un o’g’li (World Scientific Research Journal, 2025)
Abstract:  This article explores the concept of cultural codes in linguistic studies and their role in political discourse. It examines the theoretical foundations of cultural codes, their significance in shaping political narratives, and how they influence the perception of political messages across different cultural contexts. Additionally, the study highlights key researchers who have contributed to the field and discusses the implications of cultural codes in political communication.